2009
DOI: 10.1002/dvg.20578
|View full text |Cite
|
Sign up to set email alerts
|

The zebrafish dyrk1b gene is important for endoderm formation

Abstract: Nodal-signaling is required for specification of mesoderm, endoderm, establishing left-right asymmetry and craniofacial development. Wdr68 is a WD40-repeat domain-containing protein recently shown to be required for endothelin-1 (edn1) expression and subsequent lower jaw development. Previous reports detected the Wdr68 protein in multiprotein complexes containing mammalian members of the dual-specificity tyrosine-regulated kinase (dyrk) family. Here we describe the characterization of the zebrafish dyrk1b homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 50 publications
0
35
0
1
Order By: Relevance
“…WDR68 is not an exception because it binds to multiple proteins, including DYRK1A (9, 12, 13), DYRK1B (14), MEKK1 (8), HIPK2 (8), CUL4-DDB1 (6), DIAP1 (13), Drosophila atypical cadherin Dachsous (55), and TRiC/CCT (this study). Our proteomic analysis also identified many more putative WDR68-binding proteins with a wide variety of biological functions.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…WDR68 is not an exception because it binds to multiple proteins, including DYRK1A (9, 12, 13), DYRK1B (14), MEKK1 (8), HIPK2 (8), CUL4-DDB1 (6), DIAP1 (13), Drosophila atypical cadherin Dachsous (55), and TRiC/CCT (this study). Our proteomic analysis also identified many more putative WDR68-binding proteins with a wide variety of biological functions.…”
Section: Discussionmentioning
confidence: 80%
“…Previously, we found that overexpression of DYRK1A induced nuclear translocation of WDR68 in a kinase activityindependent manner (9). WDR68 regulates gene expression (7,14,63), so the binding of overexpressed DYRK1A to WDR68 in the nucleus might interfere with normal gene expression. This could partly explain how overexpressed DYRK1A affects gene expression and induces the pleiotropic phenotypes observed in Down syndrome patients.…”
Section: Down Syndrome and The Physiological Function Of Wdr68 Inmentioning
confidence: 99%
See 1 more Smart Citation
“…In the zebrafish Danio rerio , DCAF7 (official gene symbol wdr68 ) was identified as a gene essential for craniofacial development19. Downregulation of dyrk1b induced similar defects in endoderm formation as reported for wdr68 mutant animals, supporting a functional interaction of these proteins in zebrafish development20. The DCAF7 ortholog in Drosophila , CG14614 (official gene symbol wap , wings apart, also called riq , riquiqui), is essential for normal wing-vein patterning and development of the adult jump muscle21.…”
mentioning
confidence: 80%
“…37 Another strong indication that DYRK1A and DYRK1B are functionally linked with E3 ubiquitin ligases is the fact that both of them, as well as HIPK2 (but not DYRK2), have repeatedly been shown to interact with DDB1 and CUL4-associated factor 7 (DCAF7, also called WDR68 or Han11). [38][39][40][41] DCAFs are a family of more than 50 proteins that function as adaptor proteins of the CUL4-DDB1 ubiquitin ligases to mediate substrate specificity. 42 The specific function of DCAF7 as a receptor subunit of E3 ligase complexes is unknown, but one might speculate that it mediates the interaction either between the kinase and its substrate or between the kinase and but it is clear that in this case, DYRK1A and DYRK1B do not act as priming kinases for GSK3.…”
Section: Dyrk2 Initiates Protein Degradation Via the Upsmentioning
confidence: 99%